GAMBARAN TINGKAT PENGETAHUAN REMAJA TENTANG SEKS PRANIKAH PADA SISWA KELAS XI DI SMK NEGERI 1 KEDAWUNG SRAGEN - Ikrima Rahmasari; Wafroh Endah Sari; Darah Ifalahma (Universitas Duta Bangsa Surakarta, 2022)
Introduction: Premarital sex is behavior that is driven by sexual desire with the opposite sex, both kissing, groping sensitive areas, making out made by two people who love each other and are not legal in marriage. It is easy to get information from the mass media, sometimes teenagers are also encouraged to be curious and try things they don't know yet. At SMK N 1 Kedawung Sragen there are 4 students who have premarital sex. Objectives: describe the description of the level of knowledge of adolescents about premarital sex in class XI students at SMK N 1 Kedawung Sragen. Methods: The design of this study used descriptive research methods, the measuring instrument used was a questionnaire. The sample of this research is class XI students at SMK N 1 Kedawung Sragen. With a total of 78 respondents, the sampling technique was proportional random sampling and used univariate analysis. Result: Based on the analysis, it was found that the level of adolescent knowledge about premarital sex in class XI students at SMK N 1 Kedawung Sragen, namely overall respondents had good knowledge of 43 people (55%) followed by respondents who had sufficient knowledge of 27 people (35%) and respondents who less knowledgeable, namely 8 people (10%). Conclusion: that the description of the level of knowledge of adolescents about premarital sex is considered very good at SMK N 1 Kedawung Sragen. It is hoped that adolescents can increase their knowledge and not make the information obtained especially about premarital sex inappropriate. Keywords: level of knowledge, premarital sex, sexual behavior.